(untitled) (Research, Society and Development, 2024)
Cardiopulmonary Arrest (CPA) is defined as the interruption of respiratory and circulatory activities. The multidisciplinary team must participate spontaneously, recognizing the process of division of labor, favoring measures and sharing decisions made. This study aims to conduct a survey of the scientific literature regarding the importance of training the multidisciplinary team in the face of cardiopulmonary arrest. This is an integrative literature review, carried out from July to September 2024. The search strategies allowed the identification of 91 articles in the Google Scholar databases. Throughout the analysis of the titles and abstracts, applying the inclusion criteria, 9 were selected for meeting all the requirements. The results show that because the patient’s survival directly depends on the effectiveness of the team’s actions, after identification, resuscitation should begin immediately to reestablish blood circulation, as well as making concrete decisions based on scientific evidence, and reducing all factors that may put the patient’s life at risk or cause sequelae. Therefore, it is concluded that multidisciplinary action plays a fundamental role in the diagnosis, classification and direct action on patients in cardiorespiratory arrest, with the aim of reestablishing the patient’s clinical condition.